(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This paper discusses the possibility of a common European approach to end-of-life situations by focusing on the case of advance directives and physician-assisted suicide. Nevertheless, this research does not address whether end-of-life situations can be harmonized at a supranational level, the EU, or, at an international level, the Council of Europe. While this contribution gives an overview of the national legislations of advance directives in some Western European Countries, in the case of a physician assisting suicide, the research reviews the approach of the national Constitutional Courts of Austria, Italy, and Germany.